The Impact of Work Stress on Employee Engagement at PT Pacific Rubber Works - Nurul Hadi; Adrian Azhar Wijanarko (Pusat P2M Politeknik Negeri Batam, 2025)
The dynamics of the manufacturing sector in the industrial era 4.0 demand optimal management of employee engagement during complex production processes. This study analyzes the impact of work stress on employee engagement in employees of PT. Pacific Rubber Works. A quantitative explanatory method using purposive sampling involved 121 respondents, who were analyzed using simple linear regression. Results showed a very weak negative association (r = -0.106) that was not significant (t = -1.163; p = 0.247). The regression equation Y = 33.175 - 0.062X indicates that each 1-unit increase in stress decreases engagement by 0.062 units. Work stress accounted for only 1.1% of the variance in employee engagement. (R² = 0.011), while 98.9% was influenced by other factors such as job satisfaction, work-life balance, and social support. The study concluded that the impact of stress on engagement does not follow conventional linear patterns in standardized manufacturing. It is recommended that management adopt a holistic approach that emphasizes dominant contextual factors to optimize employee engagement.